2021
DOI: 10.1177/0010414021997164
|View full text |Cite
|
Sign up to set email alerts
|

Social Transformation and Violence: Evidence from U.S. Reconstruction

Abstract: How do political actors create and institutionalize revolutionary social transformation, and what are the consequences of their efforts? In this paper, we provide a framework for understanding the conditions under which revolutionary social transformation unfolds and becomes institutionalized over time. We argue that a direct consequence of social transformation and the institutionalization thereof, however, is violence against the revolution’s beneficiaries which can likewise endure over the long-term. We tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…When the vanquished do not recognize the authority of the victors or accept their vision of sovereignty, the victors will struggle to govern the vanquished. Radical Republican efforts to engineer social transformation during Reconstruction were met with violent backlash from the South that left the revolutionary project incomplete (Foner 1988; Stewart and Kitchens 2021). Following the departure of federal troops, Southern elites successfully hollowed out the bureaucratic capacity of the state, and Southern Democrats overwhelmingly elected unrepentant former Confederates to the U.S. Congress (Suryanarayan and White 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When the vanquished do not recognize the authority of the victors or accept their vision of sovereignty, the victors will struggle to govern the vanquished. Radical Republican efforts to engineer social transformation during Reconstruction were met with violent backlash from the South that left the revolutionary project incomplete (Foner 1988; Stewart and Kitchens 2021). Following the departure of federal troops, Southern elites successfully hollowed out the bureaucratic capacity of the state, and Southern Democrats overwhelmingly elected unrepentant former Confederates to the U.S. Congress (Suryanarayan and White 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having clear implications for electoral politics, backlash may take the form of violence committed against groups that are beneficiaries of egalitarian policies. To take a historical example, Stewart and Kitchens (2021) observed a positive correlation between Black literacy rates in a given county and White individuals' acts of aggression against Black people in that county during the long period of Reconstruction that followed the US Civil War. In a more recent analysis based on the United States Extremist Crimes Database, Mills et al (2020) observed a positive association between county-levels of gender parity and far-right violence in that county.…”
Section: How Policy Backlash Impedes Progress Toward Equalitymentioning
confidence: 99%
“…After the retreat from Reconstruction and the removal of federal troops, the lack of a national police power to enforce civil rights law, as we have seen, severely constrained the federal government's capacity to promote racial equality even if it had been so inclined (and it was, for the most part, decidedly not so inclined). Moreover, Reconstruction and military occupation provoked an exceedingly violent reaction on the part of white Southerners, and for most of the twentieth century, the state effectively ceded the means of coercion through violence to organized, and often sanctioned groups (such as the Ku Klux Klan) and activities (such as lynching) that obviated any possibility of real civil rights enforcement (Stewart and Kitchens 2018). Reconstruction, moreover, was viewed for much of the twentieth century as a shameful episode of corrupt and illegitimate federal overreach and not a program worth emulating.…”
Section: Coercionmentioning
confidence: 99%